Preliminary experience with the aquablation waterjet for Enlarged prostate treatment in Taiwan: A retrospective study - Pin-Chun Liu; Yi-Sheng Lin; Chao-Yu Hsu; Yen-Chuan Ou; Jing-Hui Shen; Min-Che Tung (Tungs’ Medical Journal)
Background: Aquablation (AquaBeam, PROCEPT BioRobotics, CA, USA), which utilizes machine-controlled water jets to ablate the prostate tissue, is a new technology that was approved for urologic surgery in Taiwan in May 2022. Objectives: This study aimed to explore the initial surgical outcomes of aquablation in patients with lower urinary tract symptoms, secondary to enlarged prostates. Methods: We retrospectively collected data on patients who underwent Aquablation between March 2024 and July 2024 to treat prostate enlargement with lower urinary tract symptoms (LUTS). Baseline characteristics, including age, body mass index, and preoperative prostate size, were recorded. Symptoms before and after Aquablation performance were evaluated using the International Prostate Symptom Score (IPSS), IPSS Quality of Life (QoL) questionnaire, and uroflowmetry. Data were then collected and analyzed using paired t tests with SPSS software. Results: Eighteen patients were analyzed. After Aquablation, the IPSS total scores and QoL scores significantly improved (from 17.88 to 6.15 [P = 0.00001] and from 3.88 to 1.61 [P = 0.00001], respectively), as well as the Qmax (from 10.9 to 27.44 mL/s, P = 0.0002), Qmean (from 4.81 to 11.3 mL/s, P = 0.0005), and post-void residual volume (from 118.3 to 34.3 mL, P = 0.03). Furthermore, the hemoglobin levels decreased by 1.76 g/dL, with one patient requiring blood transfusions. Meanwhile, three patients experienced complications of postoperative bleeding, requiring reoperation. Conclusion: Aquablation is a promising alternative for treating benign prostate hypertrophy in Taiwan, showing significant improvements in LUTS and voiding function.